The metabolic pathways utilized by Salmonella Typhimurium during infection of host cells. Issue 2 (23rd February 2018) - Thompson, Arthur; Fulde, Marcus; Tedin, Karsten
Summary: Only relatively recently has research on the metabolism of intracellular bacterial pathogens within their host cells begun to appear in the published literature. This reflects in part the experimental difficulties encountered in separating host metabolic processes from those of the resident pathogen. One of the most genetically tractable and thoroughly studied intracellular bacterial pathogens, Salmonella enterica serovar Typhimurium ( S . Typhimurium), has been at the forefront of metabolic studies within eukaryotic host cells. In this review, we offer a synthesis of what has been discovered to date regarding the metabolic adaptation of S . Typhimurium to survival and growth within the infected host. We discuss many studies in the context of techniques used, types of host cells, how host metabolites contribute to intracellular survival and proliferation of the pathogen and how bacterial metabolism affects the virulence and persistence of the pathogen.